Mechanisms of artemether toxicity on single cardiomyocytes and protective effect of nanoencapsulation. (24th August 2020) - Moreira Souza, Ana Carolina; Grabe‐Guimarães, Andrea; Cruz, Jader dos Santos; Santos‐Miranda, Artur; Farah, Charlotte; Teixeira Oliveira, Liliam; Lucas, Alexandre; Aimond, Franck; Sicard, Pierre; Mosqueira, Vanessa Carla Furtado; Richard, Sylvain
Abstract : Background and Purpose: The artemisinin derivative, artemether, has antimalarial activity with potential neurotoxic and cardiotoxic effects. Artemether in nanocapsules (NC‐ATM) is more efficient than free artemether for reducing parasitaemia and increasing survival of Plasmodium berghei ‐infected mice. NCs also prevent prolongation of the QT interval of the ECG. Here, we assessed cellular cardiotoxicity of artemether and how this toxicity was prevented by nanoencapsulation. Experimental Approach: Mice were treated with NC‐ATM orally (120 mg·kg −1 twice daily) for 4 days. Other mice received free artemether, blank NCs, and vehicle for comparison. We measured single‐cell contraction, intracellular Ca 2+ transient using fluorescent Indo‐1AM Ca 2+ dye, and electrical activity using the patch‐clamp technique in freshly isolated left ventricular myocytes. The acute effect of free artemether was also tested on cardiomyocytes of untreated animals. Key Results: Artemether prolonged action potentials (AP) upon acute exposure (at 0.1, 1, and 10 μM) of cardiomyocytes from untreated mice or after in vivo treatment. This prolongation was unrelated to blockade of K + currents, increased Ca 2+ currents or promotion of a sustained Na + current. AP lengthening was abolished by the NCX inhibitor SEA‐0400. Artemether promoted irregular Ca 2+ transients during pacing and spontaneous Ca 2+ events during resting periods. NC‐ATM prevented all effects. Blank NCs had no effects compared with vehicle. Conclusion and Implications: Artemether induced NCX‐dependent AP lengthening (explaining QTc prolongation) and disrupted Ca 2+ handling, both effects increasing pro‐arrhythmogenic risks. NCs prevented these adverse effects, providing a safe alternative to the use of artemether alone, especially to treat malaria. Abstract :